2021
DOI: 10.31571/bahasa.v10i2.3220
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Perceptions of Collaborative Writing during Remote Teaching

Abstract: Whether online or face-to-face, research on collaborative writing has been widely conducted to explore its theoretical and pedagogical merits for language learning. Despite positive evidence on its benefits, more studies need to explore its implementation under specific circumstances such as teaching and learning during the pandemic Covid-19. This paper reports the EFL pre-service teachers’ perceptions and attitudes of their experiences and perceived affordances of collaborative writing toward their language a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The outbreak of the COVID-19 pandemic forced many institutions to switch to emergency online teaching, demonstrating the importance of being prepared for any teaching and learning situation. As Rezeki and Surmiyati (2021) also observed, social isolation during the pandemic demotivated students in terms of participation and task completion, resulting in issues with students' writing skills development. This situation also provided the opportunity to investigate the issue differently than in earlier studies by utilizing a variety of online tools that enable social interaction through teamwork.…”
Section: Introductionmentioning
confidence: 77%
“…The outbreak of the COVID-19 pandemic forced many institutions to switch to emergency online teaching, demonstrating the importance of being prepared for any teaching and learning situation. As Rezeki and Surmiyati (2021) also observed, social isolation during the pandemic demotivated students in terms of participation and task completion, resulting in issues with students' writing skills development. This situation also provided the opportunity to investigate the issue differently than in earlier studies by utilizing a variety of online tools that enable social interaction through teamwork.…”
Section: Introductionmentioning
confidence: 77%
“…With regard to the Indonesian context, some studies (Anggraini et al, 2020;Rezeki & Surmiyati, 2021;Winarti & Cahyono, 2021) attempted to explore Indonesian students' perceptions of the CW strategy. Anggraini et al (2020) provided some evidence that their 80 EFL participants found CW helpful for them in generating writing ideas and developing their writing.…”
Section: Introductionmentioning
confidence: 99%
“…Anggraini et al (2020) provided some evidence that their 80 EFL participants found CW helpful for them in generating writing ideas and developing their writing. With similar views, Rezeki and Surmiyati (2021) explored the perceptions of CW experiences involving 36 EFL students in writing skill development classes. The result would seem to show that students had positive perceptions of the CW practice, which positively influenced their language and soft skills development.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative writing provides an opportunity for students to improve their language use and writing quality by working together with their peers (McDonough et al, 2018). In addition, students could discuss, share ideas, and even debate to get a joint agreement when they write collaboratively (Rezeki & Surmiyati, 2021). Moreover, collaborative writing allows the students to improve their understanding, willingness to listen, social skills, and respect others' ideas (Hammond et al, 2010;Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%